(untitled) (Research, Society and Development, 2022)
The use of prunings associated with the biostimulants application have been much discussed in the current scenario. The adoption of that technique can be propitious to the modern coffee growing. Even though it shows off efficiently, there are still a few studies about this association. Before what was exposed, the objective was to appraise the effect of the biostimulants application in the production components, growth and in the phytohormone concentration on coffee bushes that were subjugated to the pruning. The experiment was conducted in São Manoel farm located in the Muzambinho city. The statistic plan used was randomized block design (DBC) in a factorial scheme 3 x 2 + 1, being three fraction types of the recommended dose (1, 2 and 3 fractions) and two application ways (by leaf and by soil) and an control treatment, totalizing 7 treatments with 4 replications and 28 experimental units. The biostimulant application provided an increase of secondary plagiotropic branches in all the thirds of the plant, in both kinds of application. The biostimulant supply in one or two applications shows off better to the growth, to phytohormone concentration and to the productivity. There was an increase to the coffee bushes productivity that was treated with the biostimulant, no matter the application way and with one or two fractions.